Peran Orang Tua dalam Pendampingan Belajar Anak di Masa Pandemi Covid 19 - Novita Afkarina; Fayruzah El-Faradis (Institut Dirosat Islamiyah Al-Amien Prenduan, 2021)
The purpose of this research is to find out how to know the condition of parent who do not understand technology in accompanying their children’s learning during covid 19 more over how is the role of parent in accompanying their children’s learning during covid 19. This research method used qualitative on case study. The subjects in this study are parents in grade 1-3 MI Mambaul Ulum Desa Pakandangan Tengah. Data collection used are interview, observation and documentation. Then the data analysis includes three procedures, are: 1). Data reduction 2). Data presentation 3). conclusions. The result of this study are 1). parent who dot not understand technology and lack insight, find it difficult to accompany their children’s learning during the covid 19 pandemic so that the assistance is less than optimal. 2). As for the important role of parent in accompanying children, parent as motivator, parent as fasilitator, as place to discuss and ask question, as well as creating an conducive environment to learning